Time course study on the growth of Salmonella Enteritidis on raw vegetables used in sandwiches - Nillian, Elexson; Tuan Chilek, Tuan Zainazor; Robin, Tunung; Anyi, Ubong; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
A time course study on the growth of Salmonella Enteritidis on raw vegetables used a part of the ingredients for sandwiches at room temperature and at 4°C, with initial microbial load of log 3 and log 1 spiked onto the lettuce and cucumber slices. The growth of Salmonella Enteritidis were higher at room temperature and were dose dependent. The information obtained in this study may contribute towards food handling solutions in order to be able to control the food safety of fresh produce.